Neurodegenerative Diseases - Kishore, Uday (IntechOpen, 2013)
This book highlights the pathophysiological complexities of the mechanisms and factors that are likely to be involved in a range of neuroinflammatory and neurodegenerative diseases including Alzheimer's disease, other Dementia, Parkinson Diseases and Multiple Sclerosis. The spectrum of diverse factors involved in neurodegeneration, such as protein aggregation, oxidative stress, caspases and secretase, regulators, cholesterol, zinc, microglia, astrocytes, oligodendrocytes, etc, have been discussed in the context of disease progression. In addition, novel approaches to therapeutic interventions have also been presented. It is hoped that students, scientists and clinicians shall find this very informative book immensely useful and thought-provoking.